Comparative synthesis and properties of POSS-based fluorinated poly(ether sulfone) random terpolymers. Issue 7 (19th January 2017) - Wei, Yanfeng; Jiang, Qiyang; Hao, Jinmeng; Mu, Jianxin
Abstract : In this article, the effect of the number of trifluoromethyl groups, the attached position of trifluoromethyl to the polymer chain and the POSS content on the properties was comparatively studied. Abstract : Three series of poly(ether sulfone)s are synthesized from POSS via nucleophilic aromatic substitution polycondensation with different fluoride bisphenols. The structures of the PESs are characterized by IR, NMR and WAXD spectroscopy. The incorporation of POSS and trifluoromethyl into a poly(ether sulfone) matrix at various molar percentages of POSS result in a dramatic decrease in dielectric constant, dielectric loss as well as a significant increase in hydrophobicity of the system. The lowest dielectric constant 2.23 (1 MHz) is obtained at 40% DDSQ–6FPH–PES (molar percent content of DDSQ = 40%). The highest water contact angle 104° is obtained at 20% DDSQ–6AF–PES. Dielectric loss of most synthetic polymers is lower than 0.002. The number of trifluoromethyl groups and the attached position of these to the polymer chain also play essential roles in the dielectric properties, hydrophobicity and thermal properties. The results are discussed and interpreted in detail.